2008
DOI: 10.1080/17482960701830495
|View full text |Cite
|
Sign up to set email alerts
|

Palliative care and circumstances of dying in German ALS patients using non‐invasive ventilation

Abstract: Non-invasive ventilation (NIV) is known to improve quality of life and to prolong survival in amyotrophic lateral sclerosis (ALS) patients. However, little is known about the circumstances of dying in ventilated ALS patients. In the light of the debate on legalizing euthanasia it is important to provide empirical data about the process of dying in these patients. In a structured interview, 29 family caregivers of deceased ALS patients were asked about their own and the patient's attitude toward physician-assis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 40 publications
2
38
0
3
Order By: Relevance
“…Once patient comfort is assured, it is suggested that mandatory ventilation is withdrawn and PS reduced to zero over 5–10 min. Kuhnlein et al 289 conducted structured interviews with 29 families regarding the circumstances of dying in MND patients receiving NIV. Seventeen caregivers described the final stages and eventual death as ‘peaceful’.…”
Section: Care Planning and Delivery Of Carementioning
confidence: 99%
“…Once patient comfort is assured, it is suggested that mandatory ventilation is withdrawn and PS reduced to zero over 5–10 min. Kuhnlein et al 289 conducted structured interviews with 29 families regarding the circumstances of dying in MND patients receiving NIV. Seventeen caregivers described the final stages and eventual death as ‘peaceful’.…”
Section: Care Planning and Delivery Of Carementioning
confidence: 99%
“…ADs was a well-covered theme. Studies explored awareness of ADs, use and compliance [138], [144], [145], [146], [147], [148], [149], [150], [151], [152] and desired level of bindingness [150], [153], [154], [155].…”
Section: Resultsmentioning
confidence: 99%
“…We believe therefore that to be ethically the ethically justifiable, the termination of ventilatory treatment requires the induction of deep sedation, and this is consistent with a previous study. 5 We have described our use of morphine and sedatives in the hope of inspiring others but as Kü hnlein and colleagues 19 argue it is important to find further empirical data about the process of dying in these patients.…”
Section: Discussionmentioning
confidence: 99%